Pengembangan E-Modul Berdiferensiasi Konten Beorientasi Budaya Lokal Meboreh Dalam Materi Sistem Sirkulasi Untuk Kelas XI - Kadek Ayu Asari; Ni Putu Sri Ratna Dewi; Ajeng Purnama Heny (Lembaga Bale Literasi, 2026)
This development research aims to compile a differentiated content e-module oriented towards the local culture of Meboreh as teaching material to support learning, test the validity of the developed media, and test the practicality of the media in the learning process. The type of research used was development research (Research and Development) with the ADDIE model, which consists of 5 stages, namely the Analysis stage, the Design stage, the Development stage, the Implementation stage, and the Evaluation stage. In this study, the implementation stage was carried out through limited trials, which only covered testing the practicality of the responses of teachers and students, because the main focus of the study was on the development and initial testing of teaching materials. The research was conducted at SMA Negeri 2 Singaraja, involving grade XI students as research subjects. The validity test was conducted using Gregory's formula, involving two subject matter experts and two media experts. The assessment results showed that the Gregory Validity Coefficient (KVG) of both subject matter and media experts scored 1, which is classified as highly valid. Furthermore, the practicality test was conducted by involving three Biology teachers and 32 students for the large group test, 16 students for the small group test based on readiness categories, with each readiness category consisting of 8 students who were not yet ready and 8 students who were ready. The analysis results showed a practicality level of 94.2% from teachers, 82.7% from the large group test, 85.9% from the small group test results for the not yet ready category, 81.8% from the test results for the ready category, with an average small group test of 83.9%, which overall included the practicality test in the very practical category. Based on these results, it can be concluded that the differentiated content E-module media oriented towards local culture in the circulation system material for Grade XI is declared to be highly valid and highly practical for use as an innovative learning tool that supports the learning process of Grade XI high school students